Amelioration of Potassium Humate as Ligand Exchanger for Adsorbed P Fractions and their Relationships with Chemical Properties of an Indonesian Andisol - Putri, Elsa Kumala; Suwardi, Suwardi; Sudadi, Untung (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
Andisols are specifically characterized by a very high P adsorption capacity owing to their acidic reaction and dominance of variable-charged clay minerals. This crop cultivation problem can be overcome by potassium humate amelioration intended to exchange the adsorbed soil P fractions into the more available (labile) forms. This study aims to evaluate the effects of potassium humate application at 0, 20, 40, and 60 kg ha-1 on the dynamics of P fractions and their relationships with the chemical properties of an Indonesian Andisol. Using the Tiessen and Moir procedure, PH2O, PNaHCO3-Pi-Po, PNaOH-Pi-Po, and PHCl fractions were obtained in topsoil (0–30 cm) and subsoil (30–60 cm) samples 16 weeks after the treatment. The organic soil P (PPo) fractions tended to increase and were attributed positively to total P and negatively to base saturation (BS) at the topsoil, whilst the subsoil PPo fractions tended to increase with the decreasing soil BS. At 60 kg ha-1, the potassium humate application effectively decreased PPo and increased PPi fractions in the subsoil. The results also revealed that humic acid component of potassium humate was an effective organic ligand exchanger for the adsorbed PPo fractions that simultaneously altered soil anion-cation equilibrium in the studied Andisol. As an implication, soil P availability was increasing.